TINJAUAN YURIDIS TERHADAP LIMBAH SISA PROYEK DRAINASE DIJALAN SULTAN SULAIMAN KOTA SAMARINDA YANG MENGGANGGU DAN MEMBAHAYAKAN KESELAMATAN PENGGUNA JALAN BERDASARKAN UNDANG-UNDANG NO.22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Arif Efendi (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTthe course of the project there is always a residual waste and the remnants of materials that can not be in use anymore and waste material in the execution of the project it is this that becomes a problem. weak supervision and discipline in the activities of the project and the implementation of minimum standards and operating procedures are not done the analysis of the impact of traffic and as well as the absence of markings or traffic signs are supposed signal to the rider and driver.Measures implementing activities in providing traffic safety situation, as set in the regulation prevents it from spread to bigger problems in the form of material damage and casualties.Keywords : Implementing activities, police traffic, rider and driver